SEMINAR BY PROFESSOR HUGH POSSINGHAM FROM THE UNIVERSITY OF QUEENSLAND AUSTRALIA - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 30 January 2016 – Universiti Sains Malaysia (USM) together with The University of Queensland Australia and Australian Government Department of Education and Training will be organising a seminar by Professor Hugh Possingham entitled "Formulating and Solving Biodiversity and Ecosystem Services Conservation Problems Within Economic And Food Production Constraints" on the 4 February 2016 at the University Conference Hall (DPU) USM from 9.00 am – 12.00 pm.